Rhetoric on trial: an aristotelian insight into Najib Razak’s corruption case - Syaza Fuhat,; Juliana Abdul Wahab, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Political rhetoric plays a crucial role in shaping public discourse and perceptions of corruption. The way in which the public perceives corruption and values anti-corruption rhetoric can significantly affect their trust in political institutions and inclinations towards politicians. Thus, anti-corruption rhetoric has been recognised as a strategic tool for political parties during elections. Nonetheless, there is a recorded tension between rhetoric’s ethical and political dimensions, particularly in corrupt regimes where political rhetoric may serve various purposes. This study critically examines the rhetorical strategies employed by Najib Razak in response to his corruption allegations and the court’s verdict, thereby addressing a gap in the literature on political rhetoric within legal challenges. Through a qualitative content analysis of 21 news broadcasts from ASTRO Awani, the study applies Aristotle’s triadic model of persuasion—ethos, pathos, and logos. The findings indicate that Najib predominantly relies on logos and pathos, strategically leveraging logical reasoning and emotional appeal while minimising the use of ethos¾ethical credibility. This selective use of rhetorical strategies suggests a deliberate effort to influence public perception amid legal challenges. The study highlights the ethical concerns surrounding such rhetorical practices, particularly in democratic contexts where public trust and legal accountability are crucial. By critically analysing Najib’s rhetoric, this study contributes to a broader understanding of the intricate relationship between rhetoric, political legitimacy, and public perception, emphasising the need to scrutinise political discourse in corruption-related contexts.